Faktor-Faktor Yang Dapat Mempengaruhi Kepuasan Kerja Karyawan - Padma Dewi, Ida Ayu Gede Sri; Agustina, Made Dian Putri; Puja, I Made Suasti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Employee job satisfaction is one of the factors that influence various aspects of PT. Bank BPD Bali Mangupura Branch Office. This finding aims to determine the impact of organizational culture, teamwork, work discipline in partial and simultaneous ways on employee job satisfaction. The sample used for research is as many as 35 respondents in the credit department. This study uses data collection methods which include: observation, interviews, literature study, documentation, and questionnaires. In this research the data analysis methods used included research instrument tests, classic assumption tests, multiple linear regression analysis, coefficient of determination experiment (R2), t-test and F-test. This research states that organizational culture, teamwork, work discipline have a positive and significant impact on employee job satisfaction